A First Record of Phlebotominae from Argentinean Patagonia (Diptera: Psychodidae: Phlebotominae) - Muzon, Javier (2002)
A species of the Lutzomyia oswaldoi group is recorded from the Valcheta stream basin, Somuncura plateau, Patagonia. It represents the World southermost record of a species of Phlebotominae, apparently supporting the hypothesis about the relictual character of several components of the Somuncura plateau biota, particularly for those species belonging to the Paranaense lineages.